2020
DOI: 10.1038/s41467-020-17966-z
|View full text |Cite
|
Sign up to set email alerts
|

Forest carbon sink neutralized by pervasive growth-lifespan trade-offs

Abstract: Land vegetation is currently taking up large amounts of atmospheric CO2, possibly due to tree growth stimulation. Extant models predict that this growth stimulation will continue to cause a net carbon uptake this century. However, there are indications that increased growth rates may shorten trees′ lifespan and thus recent increases in forest carbon stocks may be transient due to lagged increases in mortality. Here we show that growth-lifespan trade-offs are indeed near universal, occurring across almost all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 68 publications
5
104
0
2
Order By: Relevance
“…In agreement with the “grow fast, die fast” hypothesis of an inverse relationship between growth (defined as woody/leaf productivity) and turnover time, we find such an inverse spatial relationship between growth and turnover time for leaves and wood across all tropical forests (Figure 6a,b). Previous studies using tree‐ring data or ground measurements suggested a similar spatial trade‐off between growth and tree life span (Brienen et al, 2020; Büntgen et al., 2019; Wright et al, 2010). However, our analysis suggests that this trade‐off exists not only at the ecosystem level but also at the organ level.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In agreement with the “grow fast, die fast” hypothesis of an inverse relationship between growth (defined as woody/leaf productivity) and turnover time, we find such an inverse spatial relationship between growth and turnover time for leaves and wood across all tropical forests (Figure 6a,b). Previous studies using tree‐ring data or ground measurements suggested a similar spatial trade‐off between growth and tree life span (Brienen et al, 2020; Büntgen et al., 2019; Wright et al, 2010). However, our analysis suggests that this trade‐off exists not only at the ecosystem level but also at the organ level.…”
Section: Resultsmentioning
confidence: 65%
“…At the plot level, carbon allocation and turnover time within the major carbon pools have been measured (Chen et al., 2013; Keeling & Phillips, 2007; Xue et al., 2017), but information on large‐scale patterns of carbon allocation and turnover is still lacking. Moreover, using tree‐ring data or ground measurements, previous studies found a trade‐off between the growth and the life span of trees (Brienen et al, 2020; Stephenson & van Mantgem, 2005), but it still remains unknown whether the hypothesis of “grow fast, die fast” holds good at the ecosystem scale.…”
Section: Introductionmentioning
confidence: 99%
“…"… Faster growth has a direct and negative effect on tree lifespan, independent of the environmental mechanisms driving growth rate variation. Growth increases, as recently documented across high latitude and tropical forests, are thus expected to reduce tree lifespans…" and that "… recent increases in forest carbon stocks may be transient due to lagged increases in mortality …" (quoted from Brienen et al, 2020).…”
Section: 'Soft' Carbon Sequestration Solutions (Nature Based)mentioning
confidence: 97%
“…Brandão et al (2013) indicate that even if the carbon storage is temporary, any carbon removal and storage from the atmosphere has the potential to mitigate climate change. However, there is firm evidence that current projections of global forest carbon sink persistence are too optimistic because the increased growth rates of trees caused by increased levels of CO2 in the atmosphere may shorten the lifespan of forest trees (Brienen et al, 2020):…”
Section: 'Soft' Carbon Sequestration Solutions (Nature Based)mentioning
confidence: 99%
“…Bezogen auf die artenschutzrechtliche Rechtfertigung des Baus und Betriebs von Windenergieanlagen bedeutet dies, dass auf die Schäden zu blicken ist, die an den genannten Schutzgütern eintreten würden, bliebe man untätig. Da der Klimawandel absehbar mit einer erhöhten CO 2 -Konzentration der Luft verbunden ist und dies Auswirkungen auf das Pflanzenwachstum hat, 71 sind die erforderlichen ursächlichen Zusammenhänge und Risiken dem Grunde nach bekannt. Daher kann es nicht erstaunen, wenn schon seit einiger Zeit landwirtschaftliche Anpassungsstrategien entwickelt werden, um die Schäden möglichst klein zu halten.…”
Section: Abwendung Erheblicher Schäden An Kulturen Viehbeständen Wäldern Fischereigebieten Und Gewässern (3 Spiegelstrich)unclassified